Echinocystic acid alleviated hypoxic-ischemic brain damage in neonatal mice by activating the PI3K/Akt/Nrf2 signaling pathway - Li, Yuan; Chen, Ling; Zheng, Da; Liu, Jian-Xia; Liu, Chao; Qi, Shao-Hua; Hu, Peng-Chao; Yang, Xiao-Fei; Min, Jia-Wei (Frontiers in Pharmacology, 2023)
Neonatal hypoxic-ischemic encephalopathy (HIE) is considered a major cause of death and long-term neurological injury in newborns. Studies have demonstrated that oxidative stress and apoptosis play a major role in the progression of neonatal HIE. Echinocystic acid (EA), a natural plant extract, shows great antioxidant and antiapoptotic activities in various diseases. However, it has not yet been reported whether EA exerts a neuroprotective effect against neonatal HIE. Therefore, this study was undertaken to explore the neuroprotective effects and potential mechanisms of EA in neonatal HIE using in vivo and in vitro experiments. In the in vivo study, a hypoxic-ischemic brain damage (HIBD) model was established in neonatal mice, and EA was administered immediately after HIBD. Cerebral infarction, brain atrophy and long-term neurobehavioral deficits were measured. Hematoxylin and eosin (H&E), terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) and dihydroethidium (DHE) staining were performed, and the contents of malondialdehyde (MDA) and glutathione (GSH) were detected. In the in vitro study, an oxygen-glucose deprivation/reperfusion (OGD/R) model was employed in primary cortical neurons, and EA was introduced during OGD/R. Cell death and cellular ROS levels were determined. To illustrate the mechanism, the PI3K inhibitor LY294002 and Nrf2 inhibitor ML385 were used. The protein expression levels of p-PI3K, PI3K, p-Akt, Akt, Nrf2, NQO1, and HO-1 were measured by western blotting. The results showed that EA treatment significantly reduced cerebral infarction, attenuated neuronal injury, and improved brain atrophy and long-term neurobehavioral deficits in neonatal mice subjected to HIBD. Meanwhile, EA effectively increased the survival rate in neurons exposed to OGD/R and inhibited oxidative stress and apoptosis in both in vivo and in vitro studies. Moreover, EA activated the PI3K/Akt/Nrf2 pathway in neonatal mice following HIBD and in neurons after OGD/R. In conclusion, these results suggested that EA alleviated HIBD by ameliorating oxidative stress and apoptosis via activation of the PI3K/Akt/Nrf2 signaling pathway.